Reliability of the electric power distribution system for alternative reserve configurations - von Schéele, Aron (My University, 2013)
This thesis addresses the reliability of the electric power distribution system in Gothenburg. Six typical loop configurations with different reserve capacities are presented and evaluated. Each loop configuration is evaluated in three different areas with different load and customer profiles. Markov modelling is used to model the reliability of the loop configurations and their respective outage time with regard to the customers. Failure and restoration statistics from the DSO in Gothenburg, Goteborg Energi Nat AB, are used as input parameters to the models of the different loop configurations. The Markov models are applied on a real case in Gothenburg with seasonal variations of the connected load. The current, existing configuration of the examined loops does not allow any additional load to be connected while still allocating for reserve capacity. Two alternatives to increase the capacity of the loops are presented as well as the economical implications of the two loop scenarios. The results show that it is feasible to connect two loops with seasonal varying loads as well as it resulting in a economically viable alternative. Thorough temperature variation calculations for the cables should be made in order to evaluate the implications of the presented alternatives.
Keywords: Elkraftteknik; Electric power engineering